The Bible in a disenchanted age: the enduring possibility of Christian faith - Moberly, Walter (Theological explorations for the Church Catholic, 2018)
Posing the problem -- Approaching the Bible -- Towards privileged perspectives -- Towards trust and truth -- Towards biblical literacy